Optimizing the Tilawati Method for Strengthening Early Childhood Psychopedagogy: A Neuro-Educational Approach at PAUD Al-Anwar, Sumber Cirebon - Ratnaningsih, Fifit Fitria; Ali, Moh.; Agung, Agung (UMSU, 2025)
This study aims to uncover detailed contextual phenomena regarding the influence of the Tilawati method on children's character and emotional regulation. A qualitative case study design was employed, utilizing participatory observation, in-depth interviews, and document analysis. The findings demonstrate that the Tilawati method enhances learning focus, self-confidence, emotional control, and cooperative behavior among learners. The structured recitation of the Qur’an in tartil rhythm also positively impacts affective balance and cognitive development. These findings suggest that the Tilawati method is a viable integrative learning model based on Islamic values and contemporary neuroscience for early childhood education.